Menggali Jejak Psikologi Lokal Perempuan Jawa dalam Sastra Indonesia: Evidensi pada Novel Kita Masih Punya Bulan Karya Nurinwa KSH - Ahmadi, Anas; Darni; Bambang Yulianto (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2021)
This article is part of a research on Indonesian literature in East Java which is studied from the perspective of local psychology. This study aims to explore local Javanese women in Indonesian literature. The research method used in this research is qualitative which leads to literature. The data collection technique was carried out in a documentative manner. The data analysis technique was carried out through the stages of identification, sorting, and exposure. The results showed that local Javanese women appeared in two segmentations, namely (1) Javanese local women as mother figures, having empathetic and patient behavior and (2) Javanese local women as child figures who had filial and patient behavior. This research shows that the local psychology of Javanese women that appears in literature leads to the psychology of eastern women which tends to strengthen intuition and ethical psychology.